Incorporating Indigenous and Non-Indigenous Worldviews Through Innovative Text Analysis: An Evaluation of Indigenous Public Health Curricula. Issue 1 (18th December 2018) - Lee, Vanessa; Coombe, Leanne; Mahoney, Ray; Allen, Craig; Robinson, Priscilla
In Australia, graduates of Master of Public Health (MPH) programs are expected to achieve a set of core competencies, designed to ensure they will be culturally safe practitioners when working with Indigenous communities. This study reviewed a sample of MPH programs to determine the level of integration that has been achieved since these core competencies were developed. In this article, we will focus on the innovative data analysis process used for the reviews. The reviews were undertaken by a national network of leading academics in Indigenous public health, including those from both Indigenous and non-Indigenous backgrounds. As each review team consisted of different members from the network, there was a need to ensure consistency in the data analysis process across all the reviews. The researchers chose to use the Leximancer V4 qualitative software data analysis tool to enhance the validity of the study outcomes. One of the limitations found using this approach was that the Indigenous voice was underrepresented in the output from the software tool; hence, a manual thematic analysis was subsequently applied to the discussion threads, to identify themes within the findings. By combining the conceptual and thematic analysis, the research team was able to bridge the gap created by the weaknesses of the two data analysis methods and incorporate both the Indigenous and non-Indigenous worldviews to the interpretation of the findings, while maintaining consistency throughout the review process.